The occurence of R577X polymorphism of ACTN3 gene in a selected group of elite fencers - Balkó, I.; Balkó, S.; Týnková, H.; Kohlíková, E. (AUC Kinanthropologica, 2014)
The presented study is focused at identifying the genetic predispositions for anaerobic performance in a group of elite fencers of the Czech Republic. Based on theoretical findings and previous studies, we assume that the identification of genetic coding can help revealing sport talents or recommend to a person interested in sport a suitable branch considering his qualifications. The study concentrates on the comparison of speed-strenght abilities determined by Wingate test performed in the Biomedical laboratory of FTVS at Charles University in Prague and specific speed tests for fencing with R577X polymorphism of ACTN3 gene in elite fencers of the Czech Republic. By the analysis of buccal smear, we found that 80% of our sample of fencers contains in their genotype at least one R allele of the ACTN3 gene of the R577X polymorphism and 27% of the whole are homozygotes with RR genotype.